2006
DOI: 10.3892/or.16.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous dermoid cyst: Cytokeratin and filaggrin expression suggesting differentiation towards follicular infundibulum and mature sebaceous gland

Abstract: Abstract. We experienced two cases of cutaneous dermoid cysts (DC). To elucidate the histogenesis of DC, we have studied cytokeratin (CK) expression in DC using ten different anti-keratin antibodies against CK1,7,8,10,14, 15, 16, 17, 18 and 19, antibody. In the cyst wall of DC, CK1 and 10 were expressed in suprabasal layer, and CK14 was limited to the basal layer. In sebaceous gland-like structures, CK14 was detected in sebaceous acinus, and CK17 was detected in sebaceous duct. The other CKs were not detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
4
8
1
1
Order By: Relevance
“…Dermoid cyst: The cyst wall and associated sebaceous gland‐like structures of dermoid cyst differentiate to follicular infundibulum (K14, K1/K10) and sebaceous glands (K14, K17), respectively, based on keratin expression (103).…”
mentioning
confidence: 99%
“…Dermoid cyst: The cyst wall and associated sebaceous gland‐like structures of dermoid cyst differentiate to follicular infundibulum (K14, K1/K10) and sebaceous glands (K14, K17), respectively, based on keratin expression (103).…”
mentioning
confidence: 99%
“…KCOT can be differentiated from cutaneous cystic lesions such as trichilemmal cyst and steatocystoma by its catagen pattern and the presence of pilosebaceous units, respectively [ 12 ], even if these develop in the buccal mucosa; however, cutaneous keratocysts resembling steatocystoma and lacking pilosebaceous units are quite difficult to differentiate from KCOT, since the corrugated anagen-like lining of these keratocysts is quite similar to that of KCOT [ 13 ]. Furthermore, the lining epithelium of steatocystoma, not of sebaceous cells, shows a similar pattern of cytokeratin expression to KCOT [ 7 , 14 ]. Cutaneous keratocysts rarely occur because once a true follicular cyst develops from the isthmus of a hair follicle, its lining possibly adopts a catagen pattern [ 13 ]; however, the ectopic development of a cutaneous keratocyst in the buccal mucosa cannot be completely excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The cyst's lumen is unilocular and lined by stratified, orthokeratotic epithelium with stratum granulosum (Figure a). Recent studies have shown that dermoid cysts have a characteristic cytokeratin profile, which suggests that they originate from the follicular infundibulum . However, lesions also frequently show “sawtooth” cornification, as seen in sebaceous gland ducts and steatocystoma (Figure b).…”
Section: Histopathology Of Congenital Dermatosesmentioning
confidence: 97%